Seventeenth Conference on Education and Training in Optics and Photonics: ETOP 2023 2023
DOI: 10.1117/12.2670468
|View full text |Cite
|
Sign up to set email alerts
|

Quantum education: how to teach a subject that nobody fully understands

Abstract: Quantum technologies are expected to be among the most transformational technologies of the twenty-first century, changing how we sense the world around us, approach security, and process critical information. Transitioning the industry from quantum research labs to the commercial environment requires a sizable workforce skilled in supporting Quantum 2.0. To achieve the goal of the entire quantum ecosystem, society at all levels needs to be aware of this emerging field and then be inspired, attracted, educated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Quantum literacy is critical to the future of quantum technology 6 . This requires that quantum resources be accessible and digestible by people at all levels and backgrounds 7 . Oqtant abstracts some of the most difficult steps in creating quantum matter so that users at different levels can still engage with the underlying quantum mechanical phenomena.…”
Section: Applications Researchmentioning
confidence: 99%
“…Quantum literacy is critical to the future of quantum technology 6 . This requires that quantum resources be accessible and digestible by people at all levels and backgrounds 7 . Oqtant abstracts some of the most difficult steps in creating quantum matter so that users at different levels can still engage with the underlying quantum mechanical phenomena.…”
Section: Applications Researchmentioning
confidence: 99%
“…Figures (7) - (10) show the details. Figure (7) shows that many participants specifically selected one or a few courses and did not decide to complete the entire program with all courses.…”
Section: Rq 2: Did the Participants Follow Given Learning Paths And O...mentioning
confidence: 99%
“…Delgado's examination of the effects of the COVID-19 pandemic on quantum information science education underscores the evolving landscape of online teaching modalities [9]. Lastly, Hasanovic's account of the NSF-funded EdQuantum project highlights efforts to develop a curriculum for future quantum technicians [10].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These included (a) relating quantum to everyday events, (b) employing active learning strategies, (c) focusing less on mathematics formulas and more on concepts, and (d) aligning quantum content with existing standards. These are echoed in Hasanovic's [36] recommendations for quantum instruction to use a visual, hands-on approach that incorporates analogies to make the content more accessible. Choudhary and colleagues [37] suggested that some quantum concepts could be taught at the middle school level, as did Farris et al [38], who studied the development of middle school curricular activities related to using quantum methods for drug discovery.…”
Section: Integrating Quantum Into K-12 Stemmentioning
confidence: 99%